2008
DOI: 10.1007/s11104-008-9547-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of maize yield response to woody and herbaceous legumes in sub-Saharan Africa

Abstract: A number of studies have tested the effect of woody and herbaceous legumes on soil fertility and maize yields in sub-Saharan Africa. However, their effects on maize productivity are much debated because results have been variable. A meta-analysis was conducted with the aim of evaluating the evidence in support of yield benefits from woody and herbaceous green manure legumes. A total of 94 peerreviewed publications from West, East and southern Africa qualified for inclusion in the analysis. Maize yield from her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(133 citation statements)
references
References 52 publications
5
127
1
Order By: Relevance
“…Notably, the technology's positive impacts appear to be more pronounced with outcome variables that are closely related with the maize crop. This is not surprising since the most common crop grown after the improved fallows is maize (Sileshi et al 2008). Maize being the staple food in Zambia and most parts of sub Saharan Africa, the contribution of the improved fallows in ensuring food security and hence alleviating food poverty cannot be over emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the technology's positive impacts appear to be more pronounced with outcome variables that are closely related with the maize crop. This is not surprising since the most common crop grown after the improved fallows is maize (Sileshi et al 2008). Maize being the staple food in Zambia and most parts of sub Saharan Africa, the contribution of the improved fallows in ensuring food security and hence alleviating food poverty cannot be over emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has been conducted into the broader frameworks of integrated soil fertility management [130][131][132][133][134][135][136][137], conservation agriculture [138][139][140][141][142][143], erosion control [144][145][146][147][148], and improved grazing management [149][150][151]. There is also a wealth of information on the benefits of specific practices such as short legume rotations (improved fallows) [152][153][154][155][156][157][158], agroforestry systems [159][160][161][162][163][164][165], and no-till systems [166][167][168][169][170]. Most of these studies, however, are short-term and geographically limited.…”
Section: Positive Trajectories and Conclusionmentioning
confidence: 99%
“…Soil management practices such as modified tillage, crop residue management, and soil nutrient status have been shown to increase water use efficiency and are a key means of adaption to periods of water stress (Hatfield et al 2001). Nutrient additions increased water use efficiency up to 25 % and conferred significant resilience of yields during Bdrought^years (Sileshi et al 2008). Studies in Africa have shown an increase in yields and rain use efficiency (RUE) with the application of mineral fertilizers, legume tree crops, or their combination (Sileshi et al 2011).…”
Section: Socio-economic Impediments To Adopting the 4rsmentioning
confidence: 99%
“…Recent varieties of soybean that produce significant amounts of leaf biomass (Krisnawati and Adie 2015), which could remain on the field as crop residue that nourishes the next crop with its nutrients, show promise in terms of crop production as well as the subsequent N benefits. Leguminous trees and cover crops in tropical cropping systems fix much more N (100-200 kg N per hectare per year) than grain legumes, providing significant N that promotes yield increases to succeeding crops (Sileshi et al 2008). Despite the N benefit as well as other benefits such as fuelwood, fodder, and weed control from some of these tree and herbaceous legumes, rates of adoption have been disappointing in many places (Kiptot et al 2007;Keil et al 2005).…”
Section: Innovative Cropping Systemsmentioning
confidence: 99%